Antecedent of Patient Revisit Intention: An Empirical Study In Dental Clinic - Ramadhani, Dwinanda Farizka; Jayanagara, Oscar (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This research aims to analyze the relationship between brand awareness, trust, brand image, social media marketing, service quality, patient satisfaction and patient revisit intention. The model constructed in this research is a newly modified conceptual framework that is referred to models or concepts from previous research that are integrated and adapted according to the condition of Omni Dental Clinic in Palembang. The model is used to test population sample of patient that revisits Omni Dental Clinic for treatment with a minimal of two visits. The sample of this research was collected using total sampling method with a total number of 146 patients. The data gathered was then performed using a method of PLS-SEM Analysis. The result acquired in this research was that all direct relationship between brand awareness, trust, brand image, social media marketing, service quality patient satisfaction and patient revisit intention was positive. The indirect effect was also positive for the relationship between trust and patient revisit intention if mediated with brand image alongside the relationship of service quality and patient revisit intention was positive with patient satisfaction as mediating variable. Trust variable has the most influence on patient revisit intention.